Corpomídia na escola: uma proposta indisciplinar - Silva, Edna Christine (2012)
Children and adolescents that experience the body as an open and complex system and also recognize the kinect matrix of thought are able to reframe their strategies of communication between body and environment, creating new cognition models and improving the learning development. This is the main hypothesis of this thesis that aims to discuss the parameters for a body education since the communication. In methodological terms, we want to ally bibliographies that study the body, the movement and its cognitive actions with researches that explain some important political discussions that belong to the communication area. Among the selected authors are Michel Foucault, who explains how the disciplinarian movement is capable to neutralize the human being potential; Rudolf Laban, who purposed the art of the movement as an improving of autonomous singular beings. Martin Barbero, who pointed the importance of testing the education since the communication. And, at long last, Antônio Damásio, among other cognitive scientists, that have been investigating how the human brain works and also its mapping system and images generation; as well as the relevance of emotions and feelings; and how it organizes the information, the memory and the learning. The questions that motivated this research emerged from the practical work that I have been developing in the last 30 years with children and adolescents. At university it was possible to notice that body language associated with the Bodymedia Theory (Katz and Greiner) that initiated the texture among several bibliographies can and must be one of the improving possibilities to the gesture/thought autonomy of children and adolescents, in all educational levels. It is regarded, thus, that the appreciation of the body movement and specifically the dance in the education can interfere in the communication strategies of perception of the world and in the cognition development